Northern timberline forests: environmental and socio-economic issues and concerns. - Kankaanpää, Sakari; Müller-Wille, Ludger; Susiluoto, Paulo; Sutinen, Marja-Liisa; McGill University, Department of Geography; Metsäntutkimuslaitos / Kolari (Metsäntutkimuslaitos, 2002)
Arktisen Neuvoston Metsänrajahankkeen loppuraportti 7 Preface 9 Introductory Remarks 14 Recommendations on Environmental and Socio-economic Issues and Concerns in Northern Timberline Forests (Ludger Mtiller-Wille) 19 Sustainable Development of the Lesotundra Zone in Russia: Problems and Opportunities (Tatiana Kouzminichna Vlassova) 40 Living at the Timberline - The Sami and the Mountain Birch Forests in Northernmost Europe (Maria Sofia Aikio and Ludger Miiller-Wille) 57 Modeling Forestry Resources with Remote Sensing and Geographic Information Systems (Shivanand Balram and John E. Lewis) 70 The World Reindeer Livelihood - Current Situation, Threats and Possibilities (Johan Mathis Turi) 76 Nordic Mountain Birch Forests (Frans-Emil Wielgolaski) 91 The Spatial Structure of the Timberline Landscape and Its Relation to Climate and Permafrost in the Usa Basin, NW Russia (Tarmo Virtanen, Kari Mikkola and Ari Nikula) 96 Russian Forest Industry and Its Threats to Timberline Forests (Alexander. I. Voropaev) 102 Assessment of Recent and Possible Future Forest Responses to Climate in Boreal Alaska (Valerie Barber, Glenn Patrick Juday, Ed Berg and Martin Wilmking) 106 Global Warming and Regional Tree-ring Growth Response in the Kola Peninsula, North-West Russia (Oleg M. Raspopov, Т. Kolström, O.L. Shumilov, I. Ju. Kirtsideli, V.A. Dergachev, M. Lindholm, J. Meriläinen, O. Eggertsson, E.A. Kasatkina, A.V. Kuzmin, G.G. Matishev, and S.L. Dzhenyuk) 113 Appendices 113 A: Paper and Poster Abstracts of the Northern Timberline Workshop in Rovaniemi, 23-25 May 2002 128 B: Northern Tree Line: The Location of the Tree Line and Its Implications for Humans 133 Russian language pages 272 С: List of Participant and Addresses / Список Участников и Адресы 279 D: Color Figures / Цветные рисунки